2016
DOI: 10.1177/0300985816646429
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 and PCNA Expression in Canine Mammary Tumors and Adjacent Nonneoplastic Mammary Glands

Abstract: The assessment of tumor proliferation has been considered a determining prognostic factor in canine mammary tumors (CMTs). However, no studies have assessed the prognostic importance of proliferation in adjacent nonneoplastic mammary glands. We included 64 CMTs (21 benign and 43 malignant) and studied the proliferation index (PI) of Ki-67 and proliferating cell nuclear antigen (PCNA) together with several clinicopathological characteristics. A positive and statistically significant correlation between the PI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 49 publications
5
46
3
Order By: Relevance
“…Tumour proliferative activity and histological grade have been described as important prognostic factors of canine and feline malignant mammary tumours . In our study, significant changes in concentrations of APP and antioxidants were detected in queens with malignant mammary tumours according with the proliferative activity (assessed by determination of mitotic counts) and the histological grade, showing that these features also influence the inflammatory and the antioxidant responses of feline mammary cancer.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Tumour proliferative activity and histological grade have been described as important prognostic factors of canine and feline malignant mammary tumours . In our study, significant changes in concentrations of APP and antioxidants were detected in queens with malignant mammary tumours according with the proliferative activity (assessed by determination of mitotic counts) and the histological grade, showing that these features also influence the inflammatory and the antioxidant responses of feline mammary cancer.…”
Section: Discussioncontrasting
confidence: 64%
“…Tumour proliferative activity and histological grade have been described as important prognostic factors of canine and feline malignant mammary tumours. 7,8,62,63 In our study, significant changes in concentrations of APP and antioxidants were detected in queens with malignant mammary tumours according with the proliferative activity (assessed by determination of mitotic counts) and the histological grade, showing that these features also influence the inflammatory and the antioxidant responses of feline mammary cancer. In dogs, significantly higher serum FRAP was described in females with malignant mammary tumours of low grade malignancy than in healthy controls, although no significant differences were detected between tumours of high grade malignancy and controls, and between tumours of highand low-grade malignancy.…”
Section: Discussionsupporting
confidence: 52%
“…32,33 A significant correlation has been noted between mitotic figure counts of carcinomas and the survival time of dogs with malignant CMTs. 34 In the present study, high c-met expression was detected in malignant CMTs within the lower mitotic index group in which the dogs had a longer survival time. Thus, c-met was assumed to be a good prognostic factor for malignant CMTs.…”
Section: Discussionsupporting
confidence: 52%
“…Mitotic count was considered as a negative prognostic indicator for human patients with breast carcinoma . A significant correlation has been noted between mitotic figure counts of carcinomas and the survival time of dogs with malignant CMTs . In the present study, high c‐met expression was detected in malignant CMTs within the lower mitotic index group in which the dogs had a longer survival time.…”
Section: Discussionmentioning
confidence: 99%
“…As the greater mammary epithelial apoptosis reduced the lactation persistency in dairy cows, it is interesting to study whether feeding cows with an RS‐based diet for a long period would reduce persistency of lactation. On other hand, the mammary expression of PCNA, which stimulates mammary epithelial proliferation, was lower in cows fed RS than in cows fed AH, indicating a possible lower mammary epithelial cell proliferation rate in RS‐fed cows. A previous study suggested feeding restriction may lead to a higher permeability in mammary gland, thus the increased mammary epithelial cell apoptosis and reduced cell proliferation in cows fed the RS‐based diet might result from the lower energy density in these animals .…”
Section: Resultsmentioning
confidence: 88%